Basic Life Support (BLS) Training Using the 'SELAMAT' Method for Integrated Health Post (Posyandu) Cadres in Mendatte Village, Enrekang Regency: Pelatihan BHD Metode SELAMAT bagi Kader Posyandu di Desa Mendatte Kabupaten Enrekang - Dominggus Dominggus; Sudirman Sanuddin; Awaluddin; Ulul Azmy; Sri Nuriana (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2026)
Emergency situations can occur anytime and anywhere, and delays in providing initial assistance may increase the risk of complications, disability, and death. In the implementation of the New Posyandu based on the six Minimum Service Standards (MSS), Posyandu cadres are expected to possess the ability to provide first aid in emergency situations. A needs assessment conducted in Mendatte Village, Enrekang Regency, revealed that none of the Posyandu cadres had previously received Basic Life Support (BLS) training and that they had limited knowledge and practical skills in emergency response. To address this problem, the “SELAMAT” Model was developed as a mnemonic-based learning medium to help cadres remember the essential steps of first aid: Survey the scene for safety, Evaluate the victim’s responsiveness, Look for and assess breathing, Activate emergency assistance, Manage Basic Life Support, Address special conditions, and Transfer the patient and ensure appropriate referral. The community service program was conducted from July 4–6, 2026, through preparation, training, simulation, mentoring, and evaluation using interactive lectures, demonstrations, hands-on practice, pocketbooks, algorithm posters, and educational videos. Evaluation was performed using pre-tests, post-tests, and practical skill observations involving 10 Posyandu cadres. The results showed that the mean knowledge score increased from 58.50 to 88.70 (p = 0.005), while the mean practical skill score reached 91.20, indicating a competent level of performance. All participants also reported that the “SELAMAT” Model was easier to understand and remember than the conventional BLS algorithm. The SELAMAT Model–based BLS training effectively improved the emergency response capacity of Posyandu cadres and has the potential to be replicated in other Posyandu settings to support the implementation of the New Posyandu and the achievement of the Minimum Service Standards in the health sector.